Bainitic transformation and generalized stability. (1st April 2023) - Zhang, Yu; He, Yuqing; Zhang, Yiyang; Song, Shaojie; Liu, Feng
Abstract: How to describe the bainitic transformation (BT) has always been considered as a key problem in designing high strength low alloyed (HSLA) steels. Here, an analytical treatment was performed to evaluate quantitatively the growth retardation of BTs, by analysis of thermodynamic driving force Δ G and kinetic energy barrier Q, in combination with modeling transformed fraction by Ravi et al. [Acta Mater. 105 (2016) 155‒164]. Unified expressions for thermo-kinetic correlation and generalized stability (GS) were derived for BT with simultaneously decreased Δ G and increased Q . By fits of the current model to experimental results, the more enduring BT comes from the higher GS, corresponding to the more sustainable BT. Based on a proposed criterion of high Δ G -high GS, the present model can be adopted to design the BT, which will produce the bainitic microstructure with high strength and high plasticity, as evidenced by the current experiments. Graphical abstract: Image, graphical abstract